ORCA-010, a Novel Potency-Enhanced Oncolytic Adenovirus, Exerts Strong Antitumor Activity in Preclinical Models - Dong, Wenliang (Mary Ann Liebert, Inc., 2014)
Improving the antitumor potency of current oncolytic adenoviruses represents one of the major challenges in development of these viruses for clinical use. We have generated an oncolytic adenovirus carrying the safety-enhancing E1AΔ24 deletion, the potency-enhancing T1 mutation, and the infectivity-enhancing fiber RGD modification. The results of in vitro cytotoxicity assays on 15 human cancer cell lines derived from different tumor types demonstrated that ORCA-010 is more potent than Ad5-Δ24RGD or ONYX-015. As ORCA-010 will initially be developed for the treatment of prostate cancer, selectivity experiments were performed using primary human prostate cells. ORCA-010 killed cancer cells more effectively than these primary human cells. In both primary prostate fibroblasts and epithelial cells, ORCA-010 was as safe as Ad5-Δ24RGD. Evaluation of ORCA-010 in in vivo xenograft tumor models in nude mice showed that ORCA-010 significantly inhibited growth of prostate, lung, and ovarian tumors and conferred prolonged survival of tumor-bearing animals. Furthermore, we observed a substantial increase in infectious viral particles in tumors injected with ORCA-010. The number of infectious viral particles increased after treatment and infectious particles remained present up to at least 4 weeks posttreatment. Intratumoral virus replication was associated with substantial necrosis and fibrosis. In conclusion, ORCA-010 is more potent than earlier generation oncolytic adenoviruses, without demonstrating increased toxicity. ORCA-010 exerted strong in vivo antitumor activity and is therefore a suitable candidate for clinical evaluation.